Human Resource Development and Management of Tertiary Education for global Competitiveness in Nigeria - Abdullahi, Nimota Jibola Kadir (Journal of Arts & Social Sciences, 2020)
This study investigated the extent to which boosting of staff morale, staff empowerment and team building served as a strategy for ensuring effective management of tertiary education for global competitiveness in Nigeria. Quantitative research design was used for the study. Seven public tertiary education institutions in Kwara State were purposely selected for the study. The view of 330 lecturers and 21 school managers were sampled through stratified and simple random sampling techniques. The population of this study comprised of 3,600 academic staff in public tertiary education institutions in Kwara State. Sample of 330 lecturers and 21 school mangers were selected with the use of Research Advisor (2006) table to determine the sample size of a known population. A self-designed questionnaire titled “Human Resource Development for Global Competitiveness Questionnaire” (HRDGCQ) was used to collect information for the study. The data collected were analyzed using t-test statistical analysis. All hypotheses were tested at 0.05 level of significance. The result revealed that there was no significant difference between the boosting of staff morale, staff empowerment, teem building and management of tertiary education for global competitiveness. It was recommended that effort should be made by government to continue boosting staff moral by providing conducive environment, proper support of staff, as well as participation of staff in organizational decision making. Staff empowerment should also be part of government priorities in the management of tertiary education. Furthermore, government and school administrators should encourage team building among lecturers so as to enhance effective management of tertiary education for global competitiveness in Nigeria.